Improved Communication and Critical Thinking Skills Based on Inquiry From Physics Education Students in Earth Physics Materials - Nor, M; Zuhdi, Zuhdi; Sartika, Medya (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to improve communication skills and critical thinking by implementing inquiry-based learning and carried out through classroom action research. This study was carried out on even semester students of earth physics courses in Riau physics education study program totaling 35 people in the 2017/2018 school year. Data collected through observation sheets and understanding concepts that were analyzed descriptively using percentages. The results of the data analysis concluded that there was an increase in communication skills by 20%. The results of the analysis of critical thinking for cycle I with 2.9% were categorized as very good and for the less well with 25.7% while for cycle II the category was very good with 40% increasing to 37.1%. Based on the results of the analysis it can be concluded that the ability of communication skills and critical thinking of students increases. This means that inquiry-based learning can improve communication skills and critical thinking in physics education students.